Resource at risk Philippine coral reefs - Rodrigo, Raul. ([Makati City] Bookmark Video, 1998)
This documentary shows how nearly all of Philippine coral reefs have been damaged by blast, cyanide, and trawley fishing. It shows the effect of this destruction on the people who make their living out of the sea. It also shows how some seaside communities have successfully saved and maintained their coral reefs.
VHS.
Keywords: Environmental sciences